Meningkatkan Hasil Belajar Lay Up Shoot Pada Permainan Bola Basket Melalui Pembelajaran Yang Dimodifikasi Menggunakan Bola Plastik Pada Siswa Sma Negeri 2 Makassar - Suardi Ambo Tang; Benny Badaru (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2021)
This study aims to determine the increase in lay ap shoot learning outcomes through the use of modified media in class XI students of SMA Negeri 2 Makassar in 2019/2020. From the results of the preliminary data (pre-test) that has been done, it shows that the students' ability in performing the lay-up movement technique is still low and this has an impact on student learning outcomes.This study uses the action research (PTK) method which can be analyzed. In this case the researcher analyzes the data by reducing the data and presenting the data in tabular form, so that the average value and percentage of learning completeness can be found. The subjects of this study were 20 students of class XI IPA at SMA Negeri 2 Makassar in 2019/2020, including 12 male students and 8 female students.The results of the research in the first cycle showed that the learning outcomes of the lay-up shoot were (41%) students who completed their studies, and (59%) students who did not complete their studies. The overall student learning outcomes in doing the lay-up shoot technique in the first cycle reached (58.82%). In cycle II shows that the learning outcomes of the lay-up shot, namely (88%) students who complete their learning, and (12%) students who do not complete their learning and overall student learning outcomes in doing the lay-up shoot technique in cycle II reach (88 , 23%).This study concludes that the use of plastic ball modification media can provide a very large and significant contribution to the learning outcomes of shoot lay-up in class XI class students of SMA Negeri 2 Makassar in 2019/2020.